Effect of Peer Counselling on Conflict Resolution among Secondary School Students in Eldoret East District - publisher, publisher; Kiprono , Jeniffer (African Journal of Education,Science and Technology (AJEST), 2015)
Strikes, unrest and student indiscipline in secondary schools have raised concern from leaders, parents, religious leaders and educators in addition to societal problems like drug abuse, HIV and AIDS. There has been advocacy for peer counselling for students to help manage social, psychological and educational problems. Consequently, this study was designed to investigate the effect of peer counselling on conflict resolution among secondary school students in Eldoret East district. The study was propounded on the basis of social learning theory by Bandura; which asserts that if peer counsellors provide good models and counselling to fellow colleagues, then they shall be imitated by peers. The study population of 3745 students in Eldoret East district was used from which a sample size of 265 students was obtained. Questionnaires were used as the main instruments of data collection. The data collected was analyzed using both descriptive and inferential statistics by using Statistical Package for Social Sciences (SPSS). Findings showed that peer counselling had significant influence on conflict resolution among the students. The study concludes that better conflict resolution is a result of effective peer counselling. It is therefore recommended that schools should adopt peer counselling to help students deal with their issues that may degenerate into indiscipline or violence which may lead to destruction of property or life hence creating peaceful school environment where the students and teachers feel comfortable to be in and where each individual rights are respected. This paper will help secondary schools through departments of guidance and counselling to consider peer counselling in resolving conflict. It will also help the Ministry of Education to develop a curriculum for peer counsellors to be implemented by all schools with an effort of strengthening peer support to Guidance and Counselling.